2011
DOI: 10.1039/c0sc00631a
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of new cyclooctynes for cell surface glycan imaging in cancer cells

Abstract: Two reagents have been synthesized for selective labeling of cell surface azidoglycans, an unusually stable version of a dibenzocyclooctyne (TMDIBO) and a third-generation difluorinated cyclooctyne (DIFO3). Both syntheses are efficient with minimal purification, and the dibenzocyclooctyne is stable under basic and acidic conditions. Flow cytometric measurements with azidosugar labeled cancer cells, in which these reagents were linked to the fluorophore Alexa Fluor 647, gave a signal-to-background ratio of up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 20 publications
3
63
1
Order By: Relevance
“…37,38 These structures vary in terms of ring strain and electron deficiency, which in turn influence reactivity toward azides and endogenous cellular molecules, such as thiols. 26 In addition, more hydrophilic cyclooctyne structures have been developed 32 to reduce the extent of nonspecific hydrophobic binding to cells.…”
Section: Resultsmentioning
confidence: 99%
“…37,38 These structures vary in terms of ring strain and electron deficiency, which in turn influence reactivity toward azides and endogenous cellular molecules, such as thiols. 26 In addition, more hydrophilic cyclooctyne structures have been developed 32 to reduce the extent of nonspecific hydrophobic binding to cells.…”
Section: Resultsmentioning
confidence: 99%
“…The azido sugar, on the other hand, was detected using a far-red fluorescently-labelled strained cyclooctyne, tetramethoxydibenzocyclooctyne (TMDIBO-647). 30 Our previous work showed the bioorthogonal nature of the isonitrile group as well as the orthogonality of the isonitrile/tetrazine reaction to the commonly used alkyne-azide chemistry under physiological conditions. 22 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…11 Several analogs of DIBO have also been reported that exhibit even higher rates of cycloaddition with azides. 5,12 …”
Section: Introductionmentioning
confidence: 99%